SOME FEATURES OF CYTOKINE PROFILE IN SEVERE PYOINFLAMMATORY DISEASES OF FACE AND NECK - L. M. Karzakova; I. A. Sidorov; A. N. Volkov; S. I. Kudrjashov (Медицинская иммунология)
Abstract. This work presents immunological data of one-hundred patients with severe pyoinflammatory diseases of face and neck area. Upon laboratory evaluation of patients with such pathology, it was shown that production of IL-1β, IL-2, IL-6, IL-8, IL-10, Rа-IL-1β is induced in this cohort. A clinically unfavorable pattern of cytokine profile was specified in patients with severe pyoinflammatory diseases of face and neck region. Its common feature is an imbalance in cytokine network associated with overproduction of immunosuppressive cytokines.